Analysis of circuit aging on accuracy degradation of deep neural network accelerator - Liu, Wenye (2020)
Deep neural networks have achieved phenomenal successes in vision recognition tasks, which motivate the deployment of deep learning in portable and smart wearable devices. To overcome the fundamental challenges of power and resource limitation, application-specific integrated circuit accelerators have emerged to compact the model and use lower precision arithmetic to increase the throughput of computation with reduced power consumption. Although very high energy efficiency has been achieved by removing redundant weights, compressing data and even sacrificing timing margin, such trend in hardware acceleration that pushes the deep learning systems to the error threshold can be disastrous for the tasks they performed due to failure or degraded performance of circuit components. Concerned by the lack of attention on the evolving unreliability effects in artificial intelligent accelerators implemented by the continuously scaled CMOS technology, this paper is the first to evaluate the effect of circuit aging on performance degradation of deep learning accelerator. Our findings indicate that DNN system running at their peak throughput rate can experience up to 84% accuracy drop after a year of aging and the accumulation of errors aggravates with the depth of learning. It is also found that relaxation of throughput rate can slow down the loss of classification accuracy considerably.